2018
DOI: 10.1016/j.bbagen.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic membrane interactions of antibacterial and antifungal biomolecules, and amyloid peptides, revealed by solid-state NMR spectroscopy

Abstract: A variety of biomolecules acting on the cell membrane folds into a biologically active structure in the membrane environment. It is, therefore, important to determine the structures and dynamics of such biomolecules in a membrane environment. While several biophysical techniques are used to obtain low-resolution information, solid-state NMR spectroscopy is one of the most powerful means for determining the structure and dynamics of membrane bound biomolecules such as antibacterial biomolecules and amyloidogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 181 publications
(231 reference statements)
0
32
0
Order By: Relevance
“…One approach to obtain well-resolved solidstate NMR spectra is to subject the sample to fast rotation around the magic angle. This method results in NMR spectra where only the isotropic chemical shifts remain which resemble those observed in solution, and similar concepts for assignment and structural analysis are used (Das et al 2015;Eddy et al 2015;Gopinath and Veglia 2015;Jaipuria et al 2017;Visscher et al 2017;Naito et al 2018).…”
Section: Solid-state Nmr Investigations Of Polypeptidesmentioning
confidence: 99%
“…One approach to obtain well-resolved solidstate NMR spectra is to subject the sample to fast rotation around the magic angle. This method results in NMR spectra where only the isotropic chemical shifts remain which resemble those observed in solution, and similar concepts for assignment and structural analysis are used (Das et al 2015;Eddy et al 2015;Gopinath and Veglia 2015;Jaipuria et al 2017;Visscher et al 2017;Naito et al 2018).…”
Section: Solid-state Nmr Investigations Of Polypeptidesmentioning
confidence: 99%
“…On one hand, CD spectroscopy provides a global view on the secondary structure, H‐bonding interactions, membrane topology, and conformation of polypeptides, where spectral changes have been used to follow conformational equilibria . On the other hand NMR spectroscopy is well established to provide structural and dynamic information on an atomic scale where distinct approaches are used to investigate polypeptides in solution or in larger complexes such as membranes, amyloid fibres, polymers, or solid surfaces …”
Section: Introductionmentioning
confidence: 99%
“…Increasing reports have indicated the mechanism of action of AMPs. Increasing studies have reported the effects of AMPs on cell membranes and organelles, with few reports on the effects of AMPs on the cell wall [40][41][42]. The microbial cell wall, which is an essential structural feature conserved among broad classes of bacteria, serves to shape the cell, mediates functional imperatives, and prevents cell lysis due to high internal osmotic pressure [43].…”
Section: Discussionmentioning
confidence: 99%